1980
DOI: 10.1017/s0021859600028604
|View full text |Cite
|
Sign up to set email alerts
|

Lactation performance of ewes and the growth of lambs, in Awassi sheep, under two different suckling regimes

Abstract: SummaryThe present study was carried out on 39 local Awassi ewes. After parturition, lambs were left to suckle their dams for the first month of age, after which they were separated into two suckling regimes, restricted and continuous.The average milk yield of ewes in the continuous system was 155·7 kg during the lactation period of 167±6·1 days whereas that of the restricted system was 139·8 kg during a lactation period of 183 ± 5·7 days. However, differences were not significant. Significant differences (P &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The overall mean values of the measured milk constituents throughout lactation, irrespective of the treatment group, were similar to those found by Zygoyiannis and Katsaounis (1986). Guirgis et al (1980) found in their study with Awassi sheep that while milk yield of ewes declined with increase in time in lactation, milk fat concentration increased. In general, it has been found that the higher the level of milk production the lower is the production of total solids, especially fat (Flamant and Morand-Fehr, 1982;Zygoyiannis and Katsaounis, 1986).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall mean values of the measured milk constituents throughout lactation, irrespective of the treatment group, were similar to those found by Zygoyiannis and Katsaounis (1986). Guirgis et al (1980) found in their study with Awassi sheep that while milk yield of ewes declined with increase in time in lactation, milk fat concentration increased. In general, it has been found that the higher the level of milk production the lower is the production of total solids, especially fat (Flamant and Morand-Fehr, 1982;Zygoyiannis and Katsaounis, 1986).…”
Section: Discussionsupporting
confidence: 86%
“…Most of this extra milk, 32-7 kg (0-83), was produced between weeks 7 and 12 and, with a milk conversion ratio of 13-6, contributed to a live weight of their kids of 2-41 kg; the remaining 6-8 kg (proportionately 0-17) was the only additional marketable milk. Folman, Volcani and Eyal (1966) and Guirgis, Kassem, Kazzal and Abdallah (1980) working with Awassi sheep on different suckling regimes showed that restriction of suckling during the first 9 or 9 to 17 weeks of lactation released considerable amounts of marketable milk. The reports on the effect of early weaning on milk production in sheep and goats are not consistent and production appears to be associated with the genotype, the nutrition and the management of the animals studied.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, los efectos del DA sobre el crecimiento del cordero y la funcionalidad del rumen han sido estudiados (16,17). Por el contrario, la información disponible sobre los posibles efectos del AR en el crecimiento del cordero antes y después del destete es muy limitada (18,19). Así pues, el objetivo de esta investigación fue determinar el efecto del amamantamiento restringido (AR) sobre parámetros de crecimiento (peso ajustado (PA) y ganancia de peso diaria (GPD)), nota de condición corporal (CC) y puntaje de FAMACHA ® (FA) durante la lactancia y pos-destete.…”
Section: Introductionunclassified